PENERAPAN MODEL EUCS DAN DELONE AND MCLEAN UNTUK MELIHAT TINGKAT KESUKSESAN DAN KEPUASAN PENGGUNA DALAM PENERAPAN APLIKASI RF MOBILE - ERIENE DHEANDA; Edi Surya Negara (P3M Institut Teknologi Pagar Alam, 2023)
Abstract− Raden Fatah Mobile is an application that helps in academic services for students of UIN Raden Fatah Palembang. This study aims to determine the level of success and satisfaction of Raden Fatah Mobile users using the End User Computing Satisfaction (EUCS) and Delone and Mclean model approaches. This research involved 18,232 students of UIN Raden Fatah Palembang who were still active students. Samples were taken using the Slovin formula with a significance level of 5%. where the models used are End User Computing Satisfaction and Delone and Mclean. The total sample is 391 active students. Furthermore, the data collected is analyzed using the Structured Equation Model-Partial Least Square (SEM-PLS) method using the smartPLS program. From the research results it is known that in the End user satisfaction model all hypotheses are accepted and all variables have a significant effect on user satisfaction, whereas in the Delone and Mclean model there are 4 hypotheses which are rejected where information quality has no effect on use and user satisfaction and also, service quality has no significant effect on use and user satisfaction. Keywords: SmartPLS; Delone and Mclean; EUCS; Raden Fatah Mobile